Identification of Cryptococcus laurenti from infected Cyprinus carpio in Fish Culture in Erbil - Iraq - Hussein H. Mala (Zanco Journal of Pure and Applied Sciences)
This study presents the first isolation of the fungus Cryptococcus laurentii from common carp Cyprinus carpio in fish ponds in Zrarati area. Erbil City, Kurdistan Region of Iraq. A total of 98 common carp specimens were collected from ponds in the region and examined for fungal infestations from September 2023 and by the end of April 2024. The identification of the fungal isolates was conducted using morphological analysis and the VITEK 2 compact system from Erbil International Hospital. The discovery of C. laurentii in common carp in Iraq signifies a novel finding, shedding light on the fungal diversity present in fish populations and aquaculture environments. The present research underscores the importance of monitoring and managing fungal infections in fish to ensure the health and sustainability of aquaculture practices in the region. The present record of species of fungi of C. laurentii is considered the first record in Iraq since no previous were seen.